Kerancuan Identitas Diaspora dalam Cerpen Randa Jarrar, Him, Me, Muhammad Ali - Fitria, Sari; Hidayah, Lutfi Nur; Arrizqina, Muhammad Jumhur; Rahmadania, Nur Dini (Universitas Putera Batam, 2023)
This study was purposed to reveal doubleness of cultural identity experienced by diaspora individuals in a short story written by Randa Jarrar, entitled Him, Me, Muhammad Ali. This story captured a life of diaspora who was not easy for a completely different culture between the homeland and the hostland. Jarrar depicted how being a Muslim living in a western country could be totally a mess for her cultural identity. To conduct this study, the method used was qualitative descriptive by collecting the data through reading the novels. Then, the certain quotations that relates to diaspora were analyzed by cultural identity and diaspora concept from Stuart Hall. This diaspora term refers to the character who owns two or more different culture in his life. The result of the analysis framed that being a diaspora living in a country with a completely different culture is complicated, especially to define the diaspora individual’s cultural of identity. The diaspora character was in the state of doubleness, which they could not completely belong to one culture. The character has culture in between his homeland (Muslim culture) and hostland (American culture). However, Jarrar depicts that there was a tendency for a culture to be more dominant than the other one.